Deslizamentos de posição subjetiva em enunciados tidos como ecolálicos de uma criança com Distúrbio de Linguagem: um estudo de caso - Bonatto, Juliana [UNESP]; Coelho, Natália Faloni; Chacon, Lourenço [UNESP] (FapUNIFESP (SciELO), 2023)
Within a linguistic-discursive framework, subject markers in a chain of utterances considered to be echolalia based on the recurring linguistic structure does X want Y? were investigated. This chain was produced during a speech therapy session by J., a female child, 10-years-old at the time of data collection, and with a speech-language pathology diagnosis of language disorder and a medical diagnosis of early psychosis. A set of linguistic fluctuations indicated a sliding of the subject position in the analyzed chain. Such fluctuations involved syntactic, lexical, semantic, morphological and prosodic elements. Discursively, the fluctuations left traces of a sliding of the subject position in the chain formed by these utterances, from a spoken subject (do you want Y?) to a speaking/desiring one (I want Y.). In this way, utterances considered echolalia can provide clues, via their linguistic fluctuations and discursive slippages, about the subject's desire in their relationship with the O/other. Given this, although they do not emerge in a conventional way, such utterances can demonstrate possibilities for changes in subject position. A contribution of the present research for clinical practice involving language in therapeutic settings therefore, was to highlight a listening to utterances, which could be seen as connected/grounded in the speech of the other. In clinical practice involving language, it is possible to create space for new/other senses for utterances, to allow the constitution of the subject of/in language, based on utterances often interpreted as being devoid of subjectivity.

Sob ótica linguístico-discursiva de orientação francesa, foram investigadas marcas de subjetividade numa cadeia de enunciados tidos como ecolálicos, ancorados na estrutura linguística recorrente X quer Y?. No interior de uma sessão de fonoterapia, essa cadeia foi produzida por J., uma criança do sexo feminino, com 10 anos de idade à época da coleta dos dados, com diagnóstico fonoaudiológico de distúrbio de linguagem e diagnóstico médico de psicose precoce. Um conjunto de flutuações linguísticas indiciaram um deslizamento de posição subjetiva na cadeia analisada. Tais flutuações envolveram elementos sintáticos, lexicais, semânticos, morfológicos e prosódicos. Discursivamente, as flutuações deixaram rastros de um deslizamento de posição subjetiva, ou seja, de sujeito falado (cê quer Y?) para falante/desejante (eu quero Y.) na cadeia formada por esses enunciados. Desse modo, enunciados tidos como ecolálicos podem dar pistas do desejo do sujeito em sua relação com o O/outro, por meio de suas flutuações linguísticas e de seus deslizamentos discursivos. Portanto, embora não irrompam de forma convencional, tais enunciados podem mostrar possibilidades de mudanças de posição subjetiva. Por conseguinte, uma contribuição da investigação relatada à clínica de linguagem é a de que, no setting terapêutico, pode haver escuta para enunciados que, em primeira instância, poderiam ser tidos como colados/enraizados no dizer do outro. Na clínica de linguagem é possível, então, dar lugar a novos/outros sentidos a tais enunciados, de maneira a favorecer a constituição do sujeito da/na linguagem a partir de enunciados frequentemente interpretados como esvaziados de subjetividade.
Subjective position sliding in utterances perceived as echolalic in a child with Language Disorder: a case study